The EU Factor in the Trade Policies of Central European Countries - Kamiński, Bartłomiej 1944- (The World Bank, 1999)
Despite strong protectionist sentiments, trade regimes have remained open in Central European countries invited to negotiate their accession to the European Union. Regional disciplines (the EU factor), combined with the legacy of low tariffs under GATT commitments, appear to have offset domestic protectionist impulses. - Kaminski examines the development of foreign trade institutions and policies in Central European countries invited to negotiate their accession to the European Union. With the dismantling of state trading, conditions of market access have been dramatically liberalized. However, except for Estonia and, to a lesser extent, the Czech Republic, most Central European countries have followed a policy of bilateral rather than multilateral trade liberalization. The fall in tariff rates on preferential imports has prompted a search for nontariff barriers, but these countries' trade regimes have remained open - which is surprising, considering the strong protectionist sentiments in economic administration. Regional disciplines (the EU factor), combined with the legacy of low tariffs under GATT commitments, appear to have been responsible for this openness. Foreign trade policy has been shaped by tensions between domestic protectionist impulses and pressures from the European Union (and other World Trade Organization members) to improve conditions of market access. This paper - a product of Trade, Development Research Group - is part of a larger effort in the group to examine trade and integration issues. The author may be contacted at bkaminski@worldbank.org